Single‐Turnover Kinetics Reveal a Distinct Mode of Thiamine Diphosphate‐Dependent Catalysis in Vitamin K Biosynthesis. (19th June 2018) - Qin, Mingming; Song, Haigang; Dai, Xin; Chan, Chi‐Kong; Chan, Wan; Guo, Zhihong
Abstract: MenD, or (1 R, 2 S, 5 S, 6 S )‐2‐succinyl‐5‐enolpyruvyl‐6‐hydroxycyclohex‐3‐ene‐1‐carboxylate (SEPHCHC) synthase, uses a thiamine diphosphate (ThDP)‐dependent tetrahedral Breslow intermediate rather than a canonical enamine for catalysis in the biosynthesis of vitamin K. By real‐time monitoring of the cofactor chemical state with circular dichroism spectroscopy, we found that a new post‐decarboxylation intermediate was formed from a multistep process that was rate limited by binding of the α‐ketoglutarate substrate before it quickly relaxed to the characterized tetrahedral Breslow intermediate. In addition, the chemical steps leading to the reactive post‐decarboxylation intermediates were not affected by the electrophilic substrate, isochorismate, whereas release of the product was found to limit the whole catalytic process. Moreover, these intermediates are likely kinetically stabilized owing to the low biological availability of isochorismate under physiological conditions, in contrast to the tight coupling of enamine formation with binding of the electrophilic acceptor in some other ThDP‐dependent enzymes. Together with the unusual tetrahedral structure of the intermediates, these findings strongly support a new ThDP‐dependent catalytic mode distinct from canonical enamine chemistry. Abstract : Over and done : Single‐turnover kinetics and quenched‐flow results provide evidence for a new post‐decarboxylation intermediate before the formation of the tetrahedral Breslow intermediate during the thiamine diphosphate dependent enzyme‐catalyzed biosynthesis of menaquinone.